(untitled) (The Strategic Review for Southern Africa, 2020)
Contemporary state building intervention in weak states is based on the assumption that once a capable state is instituted, it will be able to ensure peace. Extant literature on state capacity and civil war onset tends to confirm this assumption. However, the relation between state capacity and the onset of non-state conflict is not adequately examined in this literature. This article, which is based on findings from research undertaken by the author at the African Leadership Centre, aims to extend the existing knowledge on state capacity and civil conflict by examining the relation between state capacity and non-state conflict in subSaharan Africa using mixed methodological approaches. A statistical analysis of the correlation between three aspects of state capacity and non-state conflict is supplemented with a detailed qualitative analysis of selected states that experience non-state conflicts and those that did not. State capacity is dissected into state effectiveness, legitimacy and monopoly of the means of coercion. The result reveals that the legitimacy and effectiveness of the state are negatively correlated with nonstate conflicts in a statistically significant way. However, the qualitative analysis indicates that the role of state capacity in reducing non-state conflicts should not be over-stated. The occurrence or absence of nonstate conflicts is influenced by the interplay of multi-faceted factors related to the level of resource scarcity, the strength of customary dispute resolution mechanisms, patterns of intercommunity interaction, nature of state policies and political actors’ stake in a conflict.